Nanosheets Derived through Dissolution‐Recrystallization of TiB2 as Efficient Anode for Sodium‐Ion Batteries. Issue 2 (1st December 2021) - Suriyakumar, Shruti; Varma, Akash; Surendran, Vishnu; Jasuja, Kabeer; Shaijumon, M. M.
Abstract: Metal borides when subjected to dissolution and recrystallization exhibit a tendency to grow preferentially in lateral dimensions and form nanosheets. Such derived nanosheets exhibit unusual properties that can potentially be used in energy conversion and storage applications. Here we report boride‐based nanosheets derived from titanium diboride through a scalable one‐pot chemical approach as a sodium‐ion battery anode material. The half‐cell with TiB2 ‐derived nanosheets (TiB2 ‐NS) as anode delivers an initial discharge capacity of 252 mAh g −1 at 0.1 A g −1, and appreciable cycling stability is achieved at 1 A g −1 current density. Further, a sodium‐ion full cell assembled with TiB2 ‐NS as anode and sodium vanadium phosphate/carbon as cathode is demonstrated. The full cell delivers an energy density of 111 Wh kg −1 at a power density of 500 W kg −1 . Being the first report of its kind, our study exemplifies the rich potential that the TiB2 ‐NS deliver as an anode material upon nanoscaling and substantiates the theoretical prediction on using transition metal boride‐based anode material for sodium‐ion battery. Abstract : Metal boride nanosheets for SIB : Titanium diboride‐derived nanosheets prepared through a scalable non‐classical recrystallization approach is explored as sodium‐ion battery anode. The results uphold the theoretical predictions of boride‐based compounds as potential anodes candidates for sodium‐ion batteries.